THE RECONFIGURATION OF INTERNATIONAL TRADE LAW IN THE DIGITAL AGE: A LITERATURE REVIEW ON CROSS-BORDER E-COMMERCE REGULATION AND DATA SOVEREIGNTY CHALLENGES - Gunawan Widjaja (Adisam Publisher, 2026)
The digital age has revolutionised international trade law through the expansion of cross-border e-commerce, which demands a reconfiguration of global regulations, whilst challenges regarding data sovereignty create a fundamental conflict between the free flow of data and national control. This literature review analyses the dynamics of legal harmonisation through the WTO E-commerce Initiative, the UNCITRAL Model Law, the ASEAN Agreement on Electronic Commerce (Law No. 4/2021), as well as a comparison of the European GDPR-DSA regulations, the US sectoral approach, and Indonesia’s Personal Data Protection Law, identifying gaps in consumer protection, electronic contracts, digital taxation, and ODR dispute resolution. Key findings underscore the need for a hybrid approach combining global minimum standards with national flexibility, particularly for developing countries facing big tech dominance and regulatory fragmentation, with recommendations to strengthen the ASEAN Data Adequacy Framework and sovereign cloud infrastructure to safeguard information sovereignty amidst the liberalisation of digital trade.